Analysis effectiveness of online learning during the COVID-19 pandemic - Yudis Ghifari; Diva Aulia Amanda; Angga Hadiapurwa (Universitas Pendidikan Indonesia, 2022)
The COVID-19 pandemic has forced all countries to implement distance learning and distance restrictions to break the chain of transmission. This article researches the effectiveness of online learning during the Covid-19 pandemic and its impact on student's ability to participate in learning. The research was conducted using a survey method with a quantitative approach. The subjects of this study were active students of the Education Technology study program at the Indonesian Education University class of 2018-2020. The survey data was analyzed by measuring the variables determined using numbers and then analyzed with the applicable statistical procedures. The results showed that online learning was considered less effective because the learning materials were not delivered properly to students. This causes students not to understand the task at hand. Another point that shows the ineffectiveness of online learning is that many issues occur during online learning sessions, for example, internet connection issues, limited interaction, lack of literacy skills, and lack of motivation and productivity of students in its implementation. The level of effectiveness of online learning still can increase if the issues that occur are minimized. Student learning motivation needs to be improved so that the effectiveness of online learning can also increase.